The implementation of environmental education and green programs in schools to achieve sustainability - Denan, Zuraini; Awang, Arita Hanim; Mazlan, Muhammad Afiq Helmi; Abdul Majid, Noor Hanita; Abdul Rahim, Zaiton; Sanusi, Aliyah Nur Zafirah (American Scientific Publishers, 2017)
Environmental education is one of the solutions to sustainability. Besides having students learning in a healthier environment, it is an environmental awareness and education (EE) for the next generation. The objective of the paper is to analyse existing eco/green school program and facilities in Malaysia and neighbouring countries. The research analyses four Eco or Green Schools of similar culture, climate and geography to identify suitable criteria that can be adopted for the public school. The research methodology is based on literature review and case studies. The literature review will reveal then initiatives and development of green awareness at public schools. Case studies investigate two Eco-Schools in a conventional layout in Malaysia and two Green Schools in the rural area in Indonesia and Thailand. The findings indicate that many schools have started the awareness of environmental education. However, only few schools have the opportunity to go further in applying the green technology. To develop a holistic Eco-School in Malaysian context successfully, supports from related authorities, potential sponsors, NGO, and communities are essential. The physical environment of school in Malaysia also need total reform to incorporate climate responsive building form and material and surrounded by greenery with ample space for green activities to ensure comfort and create school itself as living laboratory.